2019
DOI: 10.1097/md.0000000000016475
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic nasogastric tube insertion for treatment of benign afferent loop obstruction after radical gastrectomy for gastric cancer

Abstract: Afferent loop obstruction is an uncommon complication associated with Billroth-II distal gastrectomy. Inappropriate treatment may result in life-threatening events as perforation and peritonitis. For the benign afferent loop obstruction, Braun or Roux-en-Y reconstruction has been reported as the choice. However, the edematous afferent loop may result in anastomotic fistula. In this study, a less invasive technique was described for treatment of benign afferent loop obstruction. The aim of this study was to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…According to Blouhos et al, 2 the causes of benign ALO are as follows: 1) post-operative adhesion, 2) internal herniation or intussusception of afferent loop, and 3) scarring due to repeated inflammation and ulceration. In addition, according to the endoscopic findings of Cao et al, 5 mucosal inflammatory edema was observed in benign ALO, which may be responsible for the occurrence of stenosis and intussusception. The author explained that postoperative anatomical changes may have been caused by erosion due to the gastric and duodenal juice, which led to mucosal injury and inflammation of the afferent loop.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…According to Blouhos et al, 2 the causes of benign ALO are as follows: 1) post-operative adhesion, 2) internal herniation or intussusception of afferent loop, and 3) scarring due to repeated inflammation and ulceration. In addition, according to the endoscopic findings of Cao et al, 5 mucosal inflammatory edema was observed in benign ALO, which may be responsible for the occurrence of stenosis and intussusception. The author explained that postoperative anatomical changes may have been caused by erosion due to the gastric and duodenal juice, which led to mucosal injury and inflammation of the afferent loop.…”
Section: Discussionmentioning
confidence: 88%
“…Endoscopic nasogastric tube insertion is an example of an endoscopic approach. 5 Among the treatments mentioned, metallic stent placement is only one to directly treat the obstruction point; however, patency typically lasts less than a year according to one report, about 9 months. 6 It can be used for only malignant ALO cases with a short life expectancy, On the other hand, it should not be used for benign ALO cases with a long life expectancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, surgery is not suitable for every patient with ALS[ 11 , 12 ]. A considerable proportion of patients could not undergo an operation because of poor physical condition, extensive peritoneal adhesions, or disseminated tumor[ 13 ]. On the other hand, for patients with acute ALS soon after operation, a secondary operation could increase the risk of anastomotic fistula, stenosis, stomatitis, and other postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…With the progress of endoscopic treatment and interventional radiology, treating ALS with endoscopic interventions has been reported recently[ 24 , 25 ]. A single-center study evaluated the effectiveness and safety of endoscopic nasogastric tube insertion and found that this technique was a conservative treatment for patients with benign ALS[ 13 ]. However, we attempted this procedure first with our patients, but the afferent loop was so twisted that the endoscope failed to pass, which is a common occurrence.…”
Section: Discussionmentioning
confidence: 99%